Current PI Control for PV Systems in DC Microgrids: A PBC Design (2019)
This paper proposes a passive PI control for applications of photovoltaic (PV) systems integrated with boost DC-DC converters. The proposed controller guarantees asymptotically stability in closed-loop for the boost DC-DC converter using Lyapunov theory. In addition, the proposed controller is robust to parametric uncertainties and unmodeled dynamics since it does not depend on the system parameters. The current control mode is selected for the PV system since it is modeled as a current source, where its current is computed as a function of solar irradiance and the cells temperature. The current reference is calculated to a perturbing and observe MPPT algorithm with a current-mode controlled to extract the maximum power available in this solar source. The PI-PBC applied to the boost DC-DC converter is compared with a classical PI approach for validating its effectiveness and the robustness. Simulation results are performed in MATLAB/Simulink with a switching frequency of 5 kHz. © 2019 IEEE.